Inspeção técnica de pulverizadores agrícolas no Rio Grande do Sul - Dornelles, Marçal Elizandro de Carvalho (2008)
The projects of inspection of agricultural sprayers projects are realized in several countries already at a long time. These projects looking to get informations and give orientations for operators that make applications with agricultural defensives with agricultural sprayers. Considering the importance that any application should be efficient and analyzing the waterways, human and food contaminations, this work are interesting to be imMarca Ented in areas where it is not accomplished still. Although, Brazil being a agricultural Country, It don t have still, agricultural legislation to this project types and that came as help; to farmers, through the optimization in the defensives applications; to the environment, for the smallest environmental contamination, due the orientation in the search of correction of problems related to the machines; and to the humanity, in general, as a consequence of healthier foods, due to the minor use of defensives on the crop productions. Several brazilian research institutions, already gave your initial contribution accomplishing this work where was verified the importance of this projects. In this line, it was realized this project looking for begin the project of technical inspection of agricultural sprayers in central region of Rio Grande do Sul State looking to get informations about use and conservation conditions of sprayers and with educational purpose, through the operator s orientation to the better machines and defensives use and looking for definition of adequate methodology to regional conditions. As conclusion, the methodology used was efficient and practical. The operator s acceptability to the project was unanimous which justify the maintenance and expansion of the project. It was determinate that only 4 sprayers (4,76%) were approved according the methodology used and the average of time of use of sprayers was of 16,79 years. The machines that were not approved presented one or more not conformities and should be corrected. Thus, the accomplishment of projects of inspection on agricultural sprayers in Brazil are very important.